Assessment of the permeability of five locally available non-sterile latex gloves used in dental practice - Ferrer, Cristina B.; Vinco, Ma. Amalia Elvira T.; Boncan, Ricardo (Adviser).
International studies have documented the presence of defects in unused latex gloves. However, little information is available regarding the various latex gloves in the Philippines. This study aims to evaluate the presence of macroporosities and size of micropores. Tests were carried out with unused gloves. Five locally available and two FDA/AD A approved brands were tested. Twenty gloves per brand were tested sequentially for permeability to air, water, dye and ions. Glove thickness and pore size were measured using the Mitutoyo micrometer and Transmission Electron Microscope, respectively. Macropores were noted with the five locally available brands containing 12% or more defective gloves. The visual tests were less critical than the electron-conductivity tests. Some gloves without obvious perforations allowed the passage of ions. Mean thickness showed that all locally available brands conformed to the thickness specifications of ASTM standards. Pore size varied significantly across brands. Variations in electrical conductivity were noted between the two ADA accepted brands and five locally available brands, indicative of microporosities. Permeability to air, water, dye and electrolyte showed that 35.09% of the locally available brands were defective. The results were subjected to the Chi-square and one way ANOVA tests (0.05 level of significance). This study tends to show that the five locally available brands tested have defective rates higher than the 4% maximum defective rate of ASTM standards.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Gloves, Surgical